COMPARISON IN DNA BARCODING, GENE EXPRESSION AND CHEMICAL OF PUERARIA MIRIFICA PLANTS - Hue Thi Thu Huynh; Thuy Thi Thu Cao; Canh Xuan Nguyen; Duong Thuy NGUYEN; Ngoc Thi Bich Nguyen; Dung Thi Thu Cao; Oanh Thi Kieu Pham; Giang Van NGUYEN (Journal of Animal and Plant Sciences, 2024)
The Pueraria mirifica plant is used as a precious material in healthcare and herbal supplement production as it is rich in phytoestrogen content. The wide cultivation gradually directs to the differences among cultivars based on their local original planting region. Besides variation in morphology, P. mirifica plants are different in phytoestrogen content. With barcoding markers located on nuclear and chloroplast, our phylogenetic analysis proved that using the group of matK, rpoC, rps16, and trnH-psbA concatenated sequences provides better discriminating power than using a single marker of common P. mirifica cultivars. Only the maximum likelihood tree based on marker combination separate P. mirifica plants from other members of the Pueraria family and separated tribes in the Fabaceae family. In addition, daidzein, genistin, and puerarin contents were recorded from the tuber of all cultivars. These results showed that some are potential cultivars for extracting phytoestrogens from the tuber. Among the five varieties studied, NA has the highest content of Daidzein and Puerarin, and TLBYT has the most difference in the sequences of rps16 and trnH-psbA and the lowest content of Puerarin, Genistin, and Daidzein. Together, qRT-PCR was performed to evaluate eight phytoestrogen biosynthesis gene expressions in leaf and tuber, in which four novel genes CHS11, CHS13, CHI2A, and UGT2 were examined for the first time in P. mirifica. These gene expressions varied depending on organs and cultivars. The differences in both the content of substances and in DNA barcodes as well as gene expression showed a clear polymorphism between varieties. The information is valuable for the selection of material sources for production.
Keywords: DNA barcoding; P. mirifica; CHS; CHI; UGT